Indications for one-stage surgery in patients with combined occlusive-stenotic lesions of the coronary and brachiocephalic artery - A. Y. Usenko; A. V. Gabrielyan; P. I. Nikulnikov; V. V. Beleevich; A. W. Ratushnyuk (Ukrainian Journal of Cardiovascular Surgery, 2016)
This article contains the results of medical pre-assesment and surgery of 35 patients with. Combined carotid and coronary arterial diseases. It includes comparative analysis and scientifically proven indications for simultaneous and staged surgical procedures in these patients.